Facile Synthesis of Highly Efficient Lepidine-Based Phosphorescent Iridium(III) Complexes for Yellow and White Organic Light-Emitting Diodes - Tao, Peng; Li, Wei-Ling; Zhang, Jing; Guo, Song; Zhao, Qiang; Wang, Hua; Wei, Bin; Liu, Shu-Juan; Zhou, Xin-Hui; Yu, Qi; Xu, Bing-She; Huang, Wei (Advanced functional materials, 2016)
Highly efficient lepidine‐based phosphorescent iridium(III) complexes with pentane‐2,4‐dione or triazolpyridine as ancillary ligands have been designed and prepared by a newly developed facile synthetic route. Fluorine atoms and trifluoromethyl groups have been introduced into the different positions of ligand, and their influence on the photophysical properties of complexes has been investigated in detail. All the triazolpyridine‐based complexes display the blueshifted dual‐peak emission compared to the pentane‐2,4‐dione‐based ones with a broad single‐peak emission. The complexes show emission with broad full width at half maximum (FWHM) over 100 nm, and the emissions are ranges from greenish–yellow to orange region with the absolute quantum efficiency (ΦPL) of 0.21–0.92 in solution, i.e., ΦPL = 0.92 (18), which is the highest value among the reported neutral yellow iridium(III) complexes. Furthermore, high‐performance yellow and complementary‐color‐based white organic light‐emitting diodes (OLEDs) have been fabricated. The FWHMs of the yellow, greenish–yellow OLEDs are in the range of 94–102 nm, which are among the highest values of the reported yellow or greenish–yellow‐emitting devices without excimer emission. The maximum external quantum efficiency of monochrome OLEDs can reach 24.1%, which is also the highest value among the reported yellow or greenish–yellow devices. The color rendering indexes of blue and complementary yellow‐based white OLED is as high as 78. Excellent fluorine‐containing lepidine‐based phosphorescent iridium(III) complexes with pentane‐2,4‐dione or triazolpyridine as ancillary ligands are designed and prepared by a facile synthetic route. These complexes exhibit greenish‐yellow to yellow emission with high phosphorescent quantum yields up to 0.92 and wide emission band with FWHM over 100 nm, which is used for fabricating highly efficient yellow and white organic light‐emitting diodes.